2022
DOI: 10.1146/annurev-genet-080320-010449
|View full text |Cite
|
Sign up to set email alerts
|

The Awesome Power of Human Genetics of Infectious Disease

Abstract: Since the identification of sickle cell trait as a heritable form of resistance to malaria, candidate gene studies, linkage analysis paired with sequencing, and genome-wide association (GWA) studies have revealed many examples of genetic resistance and susceptibility to infectious diseases. GWA studies enabled the identification of many common variants associated with small shifts in susceptibility to infectious diseases. This is exemplified by multiple loci associated with leprosy, malaria, HIV, tuberculosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 154 publications
0
10
0
Order By: Relevance
“…An advantage of the Diversity Outbred mouse population is that infection with M. tuberculosis induces phenotypes that are rare in common laboratory inbred strains of mice [15][16][17]. Further, a growing body of evidence shows similarities in M. tuberculosis-infected Diversity Outbred mice and humans in biomarkers, gene expression signatures, and BCG vaccination [38,39,67,68,91].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An advantage of the Diversity Outbred mouse population is that infection with M. tuberculosis induces phenotypes that are rare in common laboratory inbred strains of mice [15][16][17]. Further, a growing body of evidence shows similarities in M. tuberculosis-infected Diversity Outbred mice and humans in biomarkers, gene expression signatures, and BCG vaccination [38,39,67,68,91].…”
Section: Discussionmentioning
confidence: 99%
“…The disease is usually restricted to the lungs and is characterized by granuloma necrosis and cavitation, neutrophilic infiltration, and cachexia [76,77]. The genetic basis of pulmonary TB is complex and not attributable to single-gene defects that cause severe immune deficiency (i.e., Mendelian susceptibility to mycobacterial disease does not explain pulmonary TB) [15,[78][79][80][81][82][83]. Although genomewide association studies have identified loci, gene candidates, and SNPs associated with increased or decreased odds ratios for pulmonary TB, only a few (e.g., Ipr1/SP110b and HLA variants/I-A Major Histocompatibility genes) have been validated [16,[84][85][86][87][88][89][90].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For almost all infectious agents, the clinical manifestations of infection are highly variable, ranging from silent infection to lethal disease ( 25 ). The field of human genetics of infectious diseases aims to characterize the genetic variants accounting for this considerable interindividual variability.…”
Section: Human Genetics Of Infectious Diseasesmentioning
confidence: 99%
“…Genome-wide association studies (GWASs) are a powerful method to identify common genetic variants associated with risk, resistance, or other quantitative measures of infectious disease. 1 However, connecting variants identified by whole-organism GWAS to disease pathogenesis is often challenging—especially when it is unclear how the identified variants affect nearby genes or how these genes relate to the disease under investigation. To solve this, studies look among the disease-linked variants for those that associate with expression of nearby genes (called expression quantitative trait loci [eQTLs]), which can provide important clues, especially during stimulation with pathogens 2 or pathogen-associated molecular patterns.…”
Section: Introductionmentioning
confidence: 99%